Perancang Bangun Sistem Informasi Penjualan Berbasis Website pada CV. Teska Dream Group Menggunakan Metode Prototype - Brigida Merila Wardani; Dwi Agus Diartono (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The buying and selling process currently really requires an information system, one of which is Teska Florist which sells various kinds of flower bouquet products such as bouquets, standing flowers, flower boards and others. Sales at Teska Florist are still done manually, that is, customers come directly to the shop to order flower arrangements. The problem faced by Teska Florist is that when customers who come from outside the city want to order flower bouquets in large quantities, they have difficulty coming to order directly at the shop. Based on the problems above, a sales information system is needed at Teska Florist. The website-based sales information system at Teska Florist is expected to simplify the buying and selling and transaction process. The method used in the design of this information system is the prototype method. This system design uses the PHP programming language and uses the Laravel framework. Testing on this system uses black box testing with the results concluding that the functionality of the sales system has been successful as a whole.